Sport science for sports practice, teacher training and health promotion : 12th conference of Baltic Society of Sport Sciences : April 25-26, 2019, Vilnius, Lithuania : abstracts - Gražulis, Donatas (editor) (Vytautas Magnus University, 2019)
On behalf of the Baltic Society of Sport Sciences (BSSS), Vytautas Magnus University Education Academy, Lithuanian National Olympic Committee and Lithuanian Olympic Academy we have the honour to invite you to take part in the work of the 12th Baltic States Sport Science Conference "Sport Science for Sports Practice and Teacher's Training and health promotion" in Vilnius, Lithuania. Vilnius hosts the BSSS conference for the third time. Vytautas Magnus University Education Academy has the honour to assume the main responsibility for the organization the Conference. The annual event brings together the teaching staff, research fellows and doctoral students from the institutions of university-level education in the Baltic States and several other countries. Sport scientists from 25 countries already acknowledged their intention to present their study in the Conference this year: from, Germany, UK, Norway, Finland, Italy, Croatia, Spain, Austria, Slovakia, Poland, Greece, Iceland, Turkey, Israel, Brazil, Portugal, China, Chile and others. Traditionally, the Conference offers the opportunity for colleagues to learn about the research results yielded by others and to launch or renew cooperation projects. The format of the conference hopefully encourages academic discussions and interaction .between the participants and renowned scientists who have been invited to deliver keynote speeches. The Conference traditionally includes competition for the award of young scientists, who get the chance to exchange ideas and establish contacts for developing their research projects. In this e. book abstracts of conference participants presentations are published.